A Study on Performance Evaluation of Initial Public Offering (IPO) - BHADRAPPA HARALAYYA; Jeelan Basha V; Nitesh S Vibhute (Journal of Advanced Research in Public Policy and Administration, 2022)
Michelacci and Suarez (2004) showed that when an industry is growing rapidly more start-up firms try to enter and vie with one another for financing their projects. Under these circumstances VC find greater opportunities. The increased demand for VC funding could increase the cost of funds to the start-ups and they tend to go public. Initial Public offerings (IPO) has been one of most popular routes chosen for raising funds by any growing company. It is a common experience that many IPOs are underpriced. These study attempts find out the factors which influence the under pricing decision. Earlier researchers had found the influence of financial factors like ownership retention, size of the issue, age of the firm, debt-equity ratio, NAV and non- financial factors like underwriter’s reputation, venture capital funding.